PERAN GURU PAI DALAM PENGUATAN MODERASI BERAGAMA STUDI DI SMA N 1 ANAK TUHA - MU’AMALAH, HUSNUL; MAULIDIN, SYARIF; APRIAWAN , ANGGI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in strengthening religious moderation at SMA N 1 Anak Tuha. The focus of this research is how PAI teachers integrate values of religious moderation into teaching, extracurricular activities, and school programs that support the creation of a tolerant and inclusive environment. The research employs a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The results show that PAI teachers at SMA N 1 Anak Tuha play a significant role in instilling values of religious moderation, both inside the classroom through lesson materials and outside the classroom through the